CONTEMPORARY ISLAMIC EDUCATION: - Endah Kusuma Dewi; Santoso Santoso; Kasinyo Harto; Mardiah Astuti (Conciencia, 2022)
This research begins with the problem of the historical background, challenges, and strategies for increasing reform efforts in contemporary Islamic education, with the aim of research to extrapolate the historical background, challenges, and strategies for increasing reform efforts in contemporary Islamic education. While this research can provide theoretical contributions and practical contributions. Where the theoretical contribution can be used as a new paradigm for subsequent researchers to conduct studies on Contemporary Islamic Education: Historical Background, Challenges, and Strategies for Increasing Reform Efforts is very relevant and representative to be realised today, where this discipline is always up-to-date, actual, developing and updating in every era and generation. Furthermore, this research is a library research by examining various literatures related to "Contemporary Islamic Education: Historical Background, Challenges, and Strategies for Improving Reform Efforts", prioritising literature written by classical and contemporary Islamic education experts. While the methods that will be used in this research are descriptive and analytical. These two methods are not presented separately, but are actualised in an integrated manner. The descriptive method is used, because the description will provide a general illustration of the problem to be examined, then from the data it will be held a comprehensive interpretation. While the analysis method is used to look critically at various problems behind the problem in question. As for the data processing procedure, Content Analysis is used. Looking at the explanation above, the research findings are the historical background of contemporary Islamic education, especially in our country Indonesia, at the beginning, it was still carried out traditionally and the curriculum was not yet compiled as it is today. Both education in surau and pesantren. This is a challenge for this nation that must be faced by the world of education more specifically to Islamic education institutions and managers. Islamic educational institutions should be the spearhead in building the Indonesian human paradigm, because it is education that is able to give birth to good and right intellectuals in building and colouring our civilisation. There are several strategies and efforts in overcoming the challenges of contemporary Islamic education, namely first, the vision and orientation of Islamic education, second, learning strategies, third, the integration of religious and general sciences, fourth, the role of morals.